Effects of the working experience, educational background, professional titles, and hospital grades of intensive care unit doctors on clinical glucocorticoid use in acute respiratory distress syndrome. Issue 10 (11th March 2022) - Xuan, Nanxia; Zhang, Xing; Hu, Wenqing; Chen, Guodong; Wang, Yesong; Zhang, Shufang; Cui, Wei; Zhang, Gensheng
Abstract : Abstract: Although glucocorticoids are commonly used for patients with acute respiratory distress syndrome in the intensive care unit, the exact attitudes of different intensive care unit (ICU) doctors about glucocorticoid usage are largely unknown. Herein, we investigated the practice of glucocorticoid application for acute respiratory distress syndrome (ARDS) by ICU doctors in China. Questionnaires were developed and sent to ICU doctors at 45 hospitals to perform statistics and analysis. ICU doctors with more working experience and professional titles had more knowledge of ARDS. Glucocorticoids were more likely to be used for ARDS caused by chemical inhalation. Doctors with longer working experience, better educational background, and higher professional titles used fewer glucocorticoids. In addition, 97.2%of the doctors considered using methylprednisolone or hydrocortisone first, 50.9% used glucocorticoids within 24hours of onset, and 37.1% insisted that steroid therapy should last 3 to 5days. Although ICU doctors with more working experience and professional titles have a better understanding of glucocorticoid use in ARDS, the majority of clinical practices and attitudes are similar among different doctors regardless of working experience, educational background, professional titles, or hospital grades.